Pandemic Influenza Preparedness: A Patient Care and Team Training Simulation - John Mahoney; Joe Suyama; Barbara Offen (Association of American Medical Colleges, 2009)
Abstract Introduction In this unique exercise, teams of medical students treat overwhelming numbers of influenza patients in a simulated hospital setting. When students assume the working roles of nurse, nursing assistant, and physician, they immediately gain insight into two subjects that are difficult to teach: the potentially overwhelming nature of an infectious pandemic, and the vital importance of teamwork, cooperation, interdisciplinary respect, and leadership in health care endeavors. This exercise can be generalized to other circumstances, health disciplines, and levels of ability. Methods Groups of 40 students manage a 150-bed hospital, created in a lecture hall or meeting room using a new adaptable method for simulating a hospital environment. Cardboard patients come to life as staff members place paper "action flags" on each patient to indicate what treatment or evaluation is required. Students "treat" patients by bringing a matching action flag to the bedside. This simulation provides a unique venue for student learning about pandemic preparedness. It also introduces aspects of system-based care and the importance of functioning in integrated health care teams, achieving an awakening in these domains in less than two hours. Results This simulation has been conducted annually at the University of Pittsburgh School of Medicine with third-year medical students, and in several other venues. In general, this exercise has been highly successful as measured by student evaluations and faculty observations. As an example, students in one third-year class indicated that they had improved knowledge about pandemic influenza, and also developed greater understanding of broader concepts that are vastly more difficult to teach. As such a majority of these students developed greater understandings of the value of communication (77%); teamwork/collaboration (69%); interdisciplinary respect (60%); cooperation (56%); leadership (33%). Discussion The significance of this exercise as a curricular element extends beyond its role as a disaster teaching tool. Students gain appreciation for the essential roles of every member of the healthcare team in a manner that cannot easily be replicated in everyday experiences. Students can quickly gain insight into emergency preparedness and into hard-to-teach concepts such as teamwork, leadership, and interdisciplinary respect through this type of practical, team-oriented simulation.